A new genus in the braconid subfamily Miracinae from the Oriental region, with descriptions of seven new species from India and Sri Lanka - Ranjith, A.p.; Achterberg, Cornelis Van; Priyadarsanan, Dharma Rajan (Zootaxa, 2023)
A new genus in the braconid subfamily Miracinae is described from the Oriental region including a new species from south India. Additionally, six new species of the genus Centistidea Rohwer is described from India and Sri Lanka. Taxonomic keys to separate the new genus from other miracine genera, to the extant species of Rugosimirax gen. nov. and to the Oriental species of Centistidea are provided.